Fish scale derived collagen/ginsenoside Rb1 biocomposites: preparation, characterization and their hemostatic ability - Chinh, Nguyen Thuy; Tien, Nguyen Thuy; Manh, Vu Quoc; Hoang, Thai (Vietnam Journal of Science and Technology, 2021)
This paper reports the characteristics and hemostatic ability of the collagen/ginsenoside Rb1 composites with different ginsenoside Rb1 content, in which, collagen was extracted from fresh water fish scales and ginsenoside Rb1 was extracted from Panax notoginseng. Glucose and glutaraldehyde were used as crosslinking agents for collagen molecules. Infrared (IR) spectroscopy and Field emission scanning electron microscopy (FESEM) were applied to assess the functional groups, interactions and morphology of the collagen/ginsenoside Rb1 composites. Glutaraldehyde exhibits a positive effect on improvement the dispersion of ginsenoside Rb1 in collagen matrix as well as on the interactions between ginsenoside Rb1 and collagen. In addition, the biocompatibility of the collagen/ginsenoside Rb1 in simulated body fluid was evaluated by ultraviolet-visible spectroscopy (UV-Vis). The obtained result shows that ginsenoside Rb1 can release well from the composite containing 1 wt.% of ginsenoside Rb1. Besides, the hemostatic ability of the composites was also tested and discussed.